2018
DOI: 10.3389/fphys.2018.01038
|View full text |Cite
|
Sign up to set email alerts
|

The Dominant Role of Visual Motion Cues in Bumblebee Flight Control Revealed Through Virtual Reality

Abstract: Flying bees make extensive use of optic flow: the apparent motion in the visual scene generated by their own movement. Much of what is known about bees' visually-guided flight comes from experiments employing real physical objects, which constrains the types of cues that can be presented. Here we implement a virtual reality system allowing us to create the visual illusion of objects in 3D space. We trained bumblebees, Bombus ignitus, to feed from a static target displayed on the floor of a flight arena, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…These and other findings 59 , 61 63 clearly show the importance of ventral motion cues for the translational displacements of flying insects. Although less information is available for walking insects, experiments performed on desert ants Cataglyphis fortis walking in narrow tunnels showed that both the lateral and the ventral optic flow were dispensable for distance estimation 64 .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These and other findings 59 , 61 63 clearly show the importance of ventral motion cues for the translational displacements of flying insects. Although less information is available for walking insects, experiments performed on desert ants Cataglyphis fortis walking in narrow tunnels showed that both the lateral and the ventral optic flow were dispensable for distance estimation 64 .…”
Section: Discussionsupporting
confidence: 74%
“…Whether Red 100 affected negatively chromatic discrimination, interfering with the L-receptor type involved in this discrimination is unknown. VR experiments with freely flying bumblebees trained to land on a virtual horizontal blue target located on a projected achromatic checkerboard made of random pink (RGB: 255, 127, 127) and white (RGB: 255, 255, 255) squares showed that the background had no incidence on the bees’ performance 61 . In this case, the pink light used could potentially stimulate all receptor types and thus truly affect the color vision system, contrarily to our red light (RGB: 255, 0, 0).…”
Section: Discussionmentioning
confidence: 99%
“…This also indicates that static elements in the insect's field of view such as bezels, capillaries, and the camera did not evoke any gaze fixation as evidenced by the lack of any specific direction in this landscape and as observed in previous VRs (10,(23)(24)(25)(26). However, when provided a tree, flies fixated on and approached the tree, and exhibited stereotypical object avoidance/landing responses with rapid saccades (rapid body turns within the tree canopy) and foreleg extension when within <10 cm of elements in the canopy (35,36) This indicates that flying insects can distinguish, navigate, and respond to virtual 3D objects from the surrounding visual scenery. In a world with two identical trees, flies oriented and approached both trees equally, as described previously for field behavior ( 22 Along with a pest (apple fly), we also measured localization of virtual tree-like objects in a crane fly (P. laeta; S3) and for a disease vector (male mosquito, A. aegypti; Fig.…”
Section: Localization Of Virtual Ecologically Relevant Objects In a Complexsupporting
confidence: 58%
“…make objects appear, disappear, or even be at apparent distances) in freely walking and flying insects. For instance, flying bumblebees (Bombus terrestris) can be trained to search for virtual feeding platform or avoid virtual obstacles displayed on a screen on the ground of a flight arena (Frasnelli et al, 2018).…”
Section: Virtual Reality On Freely Moving Insectsmentioning
confidence: 99%